Identification of luteolin-7-glucoside metabolites after oral administration and development of a method for their quantitative analysis - G. V. Adamov; O. L. Saybel; A. N. Babenko; E. S. Melnikov; A. I. Radimich; O. Yu. Kulyak; L. V. Krepkova (Разработка и регистрация лекарственных средств)
Introduction. The development and registration of antiviral drugs is an urgent task. Flavonoids, in particular, luteolin-7-glycoside (cinaroside, luteolin-7-O-glycoside) demonstrate high broad-spectrum antiviral activity in vitro, and the industrial regulations for the production of luteolin-7-glycoside from the leaves of holly willow have already been developed at the VILAR. One of the problems with the introduction of flavonoids into medical practice is their low bioavailability and intensive biotransformation. Existing publications provide contradictory data on the pharmacokinetics of luteolin-7-glycoside, and therefore our own research was conducted.Aim. To develop a methodology for the quantitative analysis of luteolin-7-glycoside and its metabolites in blood plasma and to test it on laboratory animals.Materials and methods. Animal experiments were carried out in accordance with the requirements of the "Guidelines for conducting preclinical studies of medicines". To develop a method of analysis and further clarify the time intervals of blood sampling, time points were analyzed: 30, 60 minutes, 2, 4, 8, 24 hours after administration of the test substance. Tubes with citrate blood of laboratory animals were centrifuged at 2000 rpm for 10 minutes. The plasma was placed in an Eppendorf-type test tube, frozen and stored at –20 °C until chromatographic analysis was performed. Blood plasma sample preparation was carried out by precipitation with methyl alcohol, the supernatant was chromatographically separated on a column Luna® 5 µm C18 column 100 Å 250 × 4.6 mm in a gradient mode in a water-acetonitrile system and a modifier – 0.2 % formic acid. The metabolites were identified by high-performance liquid chromatography with mass spectrometric detection. To do this, the spectral characteristics of the peaks that appeared on the chromatograms of blood plasma samples after oral administration of luteolin-7-glycoside were interpreted. The concentration of the analyzed substances was assessed by the internal standard method, which was rutin. To determine the concentration of luteolin, a standardized luteolin substance was used as a standard sample, the concentration of the remaining metabolites was estimated in terms of luteolin.Results and discussion. It was found that after oral administration of luteolin-7-glycoside in starch paste to laboratory animals, native luteolin-7-glycoside was not detected in blood plasma. The main metabolites were luteolin-diglucuronide and luteolin-glucuronide, their maximum plasma concentrations are about three times higher than luteolin and methyllyuteolin-diglucuronide. The results are compared with data from other studies.Conclusion. The absence of native luteolin-7-glycoside in blood plasma after oral administration makes it necessary to seriously reconsider the relevance of the conclusions obtained during studies of its activity in vitro. However, in the presence of antiviral activity in vivo, there is an urgent need for further research to establish the real mechanisms of action of this medicinal substance.